1983
DOI: 10.1159/000238194
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Methioprim in Human Volunteers

Abstract: The pharmacokinetics of methioprim have been studied in 11 healthy volunteers who received tablets of 320 mg as a first dose followed by 160 mg every 12 h. The concentrations were measured in plasma and skin blisters formed by suction, by high-pressure liquid chromatography. The mean individual peak concentrations during approximate steady state on the fourth day were 2.7 mg/l in serum and 1.3 mg/l in blister fluid. At steady state, 7.1 % of the dose was recovered in urine during the dosage interval of 12 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Elimination of brodimoprim was slower than reported for other dihydrofo late reductase inhibitors like trimethoprim [2,11,12] and methioprim [13]. The pres ent ti/2 of brodimoprim was approxi mately 3 times that of trimethoprim in pre vious studies [3,14], Contributing to the longer t|/2 of brodimoprim is a higher pro tein binding (89% for brodimoprim vs. 45% for trimethoprim) [14], The slightly lower affinity of brodimoprim to the hu man dihydrofolate reductase affinity tends in the opposite direction.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Elimination of brodimoprim was slower than reported for other dihydrofo late reductase inhibitors like trimethoprim [2,11,12] and methioprim [13]. The pres ent ti/2 of brodimoprim was approxi mately 3 times that of trimethoprim in pre vious studies [3,14], Contributing to the longer t|/2 of brodimoprim is a higher pro tein binding (89% for brodimoprim vs. 45% for trimethoprim) [14], The slightly lower affinity of brodimoprim to the hu man dihydrofolate reductase affinity tends in the opposite direction.…”
Section: Discussionmentioning
confidence: 69%
“…The pres ent ti/2 of brodimoprim was approxi mately 3 times that of trimethoprim in pre vious studies [3,14], Contributing to the longer t|/2 of brodimoprim is a higher pro tein binding (89% for brodimoprim vs. 45% for trimethoprim) [14], The slightly lower affinity of brodimoprim to the hu man dihydrofolate reductase affinity tends in the opposite direction. As a conse quence of the slow elimination, therapeu tic brodimoprim concentrations were maintained for more than 24 h, and even after 48 h the concentrations exceeded the minimum inhibitory concentrations (MICs) of several pathogenic bacteria [1], Penetration to blister fluid was marked; the invasion rate corresponded to a dou bling time of 2.6 h, which is 3 times above that of methioprim found in a similar suc tion blister model [13]. The peak concen tration in blister fluid being approxi mately 1/3 of the peak in serum, and an AUCbiister of 73% of the AUCserum also exceeded the values for methioprim.…”
Section: Discussionmentioning
confidence: 91%
“…The metabolism of MTP in the two animal species is also more extensive than in man who excretes 20-27% unchanged MTP in urine after intravenous administration of a single dose (Plozza-Nottebrock et al 1981). From a study with oral administration of MTP to human volunteers Bruun et al (1983), however, reported that only 7% of the dose was excreted as unchanged drug under steady state conditions. The major metabolite of MTP in urine from both pigs and goats was found to be metioprim sulfoxide.…”
Section: Discussionmentioning
confidence: 99%
“…198 1). Clinical investigations in man have shown MTP to have a longer half-life than TMP -10 hrs versus 7 hrs (Andreasen et al 1978;Bishop-Freudling & Vergin 1981;Plozza-Nottebrock et al 1981;Bruun et al 1983). In domestic animals TMP is eliminated much faster than in man (Baggot 1982), and also much faster than the sulfonamides in combination with which it is used in veterinary practice (Nielsen & Rasmussen 1976).…”
mentioning
confidence: 99%